Swelling and diffusion studies of poly(N-isopropylacrylamide/itaconic acid) copolymeric hydrogels in water and aqueous solutions of drugs - KAYAMAN APOHAN, NİLHAN (JOHN WILEY & SONS INC, 2004)
N-Isopropylacrylamide/itaconic acid hydrogels (NIPAAm/IA) containing different amounts of itaconic acid prepared by irradiating with gamma-radiation were used in experiments on swelling and diffusion of the model drugs methylene blue, lidocaine, and sildenafil citrate (VIAGRA). The NIPAAm/IA hydrogels containing 0-3 mol % itaconic acid irradiated at 48 kGy has been used for swelling and diffusion studies in water and aqueous solutions containing the above-mentioned model drugs. For these hydrogels, swelling studies indicated that swelling increased with the following order: water > lidocaine > methylene blue > VIAGRA. Diffusions of water and the drugs within hydrogels were found to be non-Fickian in character. (C) 2003 Wiley Periodicals, Inc. J Appl Polym Sci 91: 911-915, 2004.
Keywords: hydrogels; radiation; diffusion; POLYMERS; RELEASE; TRANSPORT